اجتہادی مسائل میں نظریہ وحدت وتعدد حق : The Theory of Multi-Valued and Single-Valued Truth in Juristic Problems - Osama Hashmi; Dr. Muhammad Sajjad (MEI, 2023)
The research outlined the opinion of Muslim Jurists in the context of Multi-Valued Truth in Jurisprudential Problems. There are two methodologies in Jurisprudential Problems, namely Multi-Valued Truth and Single-Valued Truth. Both of these theories are followed by a number Muslim Jurists, who have presented their arguments from Qurʾān, Sunnah, Customs of Companions of Prophet (PBUH) and behavior of Jurist Imams. A comparative study of both of these methodologies revealed the fact that the view point of follower of Multi-Valued Truth is convincing due the presence of sound arguments, including explicit support from Qurʾān and Ḥadīth, direct inference and abundance of arguments. Moreover, the proponents of Multi-Valued Truth also analyzed and answered the objections of followers of Single-Valued Truth, which revealed the fact that most of these objections belong to Rigidity and Concession. However, all Jurisprudential Problems are not included in Multi-Valued Truth, rather, some are excluded from its domain, for instance implementation of law, judicial system, permissible and non-permissible items etc. On the other hand, most of the matters of personal lives of people fall under the category of Multi-Valued Truth.